SPIRITUALITAS DITENGAH TANTANGAN MODERN - Frans, Imanuella R (Institut Agama Kristen Negeri (IAKN) Ambon, 2023)
Abstract:The importance of religion for individuals shows a positive correlation with feelings of depression (personal distress), belief in the existence of God has a curvelinear relationship with feelings of depression (personal distress). And feeling meaningful has a negative correlation with feeling depressed. Other religiosity and spirituality variables did not correlate with feelings of depression (dependence on great powers, belief in life after death, belief in heaven and hell, visits to places of worship, frequency of prayer, rebirth as a Christian, and current religious choice). . Modernism is seen as a